The Constraints-Led Approach : Principles for Sports Coaching and Practice Design - Renshaw, Ian; Davids, K. (Keith), 1953-; Newcombe, Daniel (Daniel J.); Roberts, Will (William M.) (Routledge studies in constraints-based methodologies in sport, 2019)
"A Constraints-Based Methodology for Sport provides students and practitioners with the theoretical knowledge required to implement constraints-led approaches in their work. Seeking to bridge the divide between theory and practice, the book sets out an 'environment design framework', including practical tools and guidance for the application of the framework in coaching and skill acquisition settings. It includes chapters on constraints-led approaches in coaching children, golf, athletics and hockey, and provides applied reading for undergraduate and postgraduate students of motor learning, skill acquisition and developing sport expertise"--